IMPLEMENTASI DIVERSIFIKASI PRODUK PONSEL PINTAR DALAM MEMENANGKAN PASAR MASA COVID-19 - Arfi Syahputra; Pristiyono Pristiyono; Junita Lubis (Departemen Manajemen, 2021)
The smartphone business during the Covid-19 pandemic can be said to be quite safe, this can be seen from the stability of smartphone users and even smartphone-producing company vendors continue to innovate to diversify products. This study seeks to measure the extent of the advantages of smartphone diversification in terms of price, product quality, satisfaction and its impact on smartphone purchasing decisions during the Covid-19 pandemic. This study took a sample of 100 Vivo smartphone users using purposive sampling technique and using primary data in the form of a questionnaire (google form). To determine the effect of each variable, the researcher applied a path analysis approach with IBM SPSS and AMOS. The final conclusion of this paper concludes that product diversification has a significant effect on prices. However, product diversification does not have a significant effect on purchasing decisions. In addition, although product quality has a significant effect on prices, it does not have a significant effect on purchasing decisions. Furthermore, the price is always a benchmark for consumers in making decisions in choosing the desired product